Sub-seasonal variations of the tropical storm track in the western north Pacific - WANG, BIN; WU, LIGUANG (MAUSAM, 1997)
With 20-year (1975-94) climatological data, we demonstrate that the tropical storm track over the western North Pacific (0° - 40°N, 100 - 180°E) exhibits prominent sub-seasonal variations on a time scale of about 40 days from May to November. The storm track variability is regulated by the conspicuous Climatological Intra Seasonal Oscillation (CISO) in the strength of the western North Pacific summer monsoon and the associated position of the western Pacific Sub-tropical High. The CISO cycle regulates the number of tropical storm formation during the Pre-Onset and Withdraw Cycles but not during the Onset and Peak Monsoon Cycles (from mid-June to mid-September).